Commensal Lactobacilli Metabolically Contribute to Cervical Epithelial Homeostasis in a Species-Specific Manner - Nicole R. Jimenez; Jason D. Maarsingh; Paweł Łaniewski; Melissa M. Herbst-Kralovetz (mSphere, 2023)
ABSTRACT In reproductive-age women, the vaginal microbiome is typically dominated by one or a few Lactobacillus species, including Lactobacillus crispatus, Lactobacillus iners, Lactobacillus paragasseri, Lactobacillus mulieris, and Lactobaccillus crispatus, has been associated with optimal cervicovaginal health; however, much is still unknown about how other lactobacilli metabolically contribute to cervicovaginal health. We hypothesized that metabolites of each Lactobacillus species differ and uniquely contribute to health and homeostasis. To address this hypothesis, we utilized a human three-dimensional (3D) cervical epithelial cell model in conjunction with genomics analyses and untargeted metabolomics to determine the metabolic contributions of less-studied vaginal lactobacilli—L. iners, L. paragasseri, and L. mulieris. Our study validated that vaginal lactobacilli exhibit a close phylogenetic relationship. Genomic findings from publicly available strains and those used in our study indicated that L. iners is metabolically distinct from other species of lactobacilli, likely due to a reduced genome size. Lactobacilli and mock controls were distinguishable based on global metabolic profiles. We identified 95 significantly altered metabolites (P < 0.05) between individual lactobacilli and mock controls. Metabolites related to amino acid metabolism were shared among the lactobacilli. N-Acetylated amino acids with potential antimicrobial properties were significantly elevated in a species-specific manner. L. paragasseri and L. iners shared aromatic, but not carbohydrate-derived, lactic acid metabolites with potential antimicrobial properties that may contribute to homeostasis of the cervicovaginal environment. Additionally, L. iners uniquely altered lipid metabolism, which may be a sign of adaptation to the cervicovaginal niche. Overall, these findings further elucidate the metabolic contributions of three key vaginal Lactobacillus species in gynecological health. IMPORTANCE Lactobacillus species contribute to cervicovaginal health by their production of lactic acid and other antimicrobial compounds. Yet, much is still unknown regarding the metabolic potential of lesser-studied but common vaginal lactobacilli. Here, we used untargeted metabolomics coupled with our 3D cervical epithelial cell model to identify metabolic differences among vaginal Lactobacillus species (Lactobacillus iners, Lactobacillus paragasseri, and Lactobacillus mulieris) and how those differences related to maintaining homeostasis of the cervical epithelium. Human 3D cell models are essential tools for studying host-bacteria interactions and reducing confounding factors inherent in clinical studies. Therefore, these unique models allowed us to decipher the putative lactobacilli mechanisms that contribute to their roles in health or disease. Metabolic analyses revealed distinct profiles of each Lactobacillus species but also shared metabolic contributions associated with antimicrobial activity: amino acid metabolism, N-acetylated amino acids, and aromatic lactic acids. These patterns provided validation of metabolites associated with health in clinical studies and provided novel targets, including immunomodulatory and antimicrobial metabolites, for postbiotic therapies.